Normal complement C4 values do not exclude hereditary angioedema. Issue 2 (27th January 2004) - Karim, Y; Griffiths, H; Deacock, S
Abstract : This report describes a patient with hereditary angioedema (HAE) in whom complement C4 values were consistently normal. There was a family history of HAE, for which the patient had previously been screened, but in view of her normal C4 values she was deemed unaffected. However, at 10 years of age she presented with an eight month history of episodes of swelling affecting her hands and recurrent episodes of abdominal pain over the previous few months. In view of the recent clinical history of swellings and the family history of HAE, C4 and C1 inhibitor (C1inh) were measured. The C4 concentration was found to be within the normal range but the C1inh value was low (0.07 g/litre; normal range, 0.18–0.37). The patient was started on tranexamic acid and at an outpatient review three months later her episodes of swelling were occurring less often and were less severe. Although recent papers have suggested that the diagnosis of HAE can be excluded if complement C4 concentrations are normal, this case highlights the fact that C4 concentrations can be normal in this condition, and it is recommended that both C4 and C1inh concentrations should be measured to exclude HAE.